deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Marine snow as vectors for microplastic transport: Multiple aggregation cycles account for the settling of buoyant microplastics to deep‐sea sediments - Nan Wu; Stuart W. D. Grieve; Andrew J. Manning; Kate L. Spencer (Limnology and Oceanography, 2025)
Many studies have reported the paradoxical observation of high concentrations of low‐density microplastics (plastic particles μ m in diameter can reach the ocean bottom. This theoretical model refines our ability to predict and understand the global and long‐term fate, transport, and inventory of microplastics in the ocean interior, the influence of microplastics on the biological carbon pump and the efficacy of plastic management policies.